Pola Asuh Orang Tua dan Perilaku Delinkuensi - Rabiyanur Lubis (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2011)
This article will explain the influence of parenting behavior of parents toward delinquency. Of this article can be concluded that the developments that occur in adolescents, if not get the control and guidance of parents will actually bring teens to the behaviors delinquency, because teenagers will take decisions based on emotion, based on the value of youth groups, based his thought, which not infrequently in conflict with social norms